A New Set of Intravascular Ultrasound-Derived Anatomical Criteria for Defining Functionally Significant Stenoses in Small Coronary Arteries: Results from Intravascular ultrasound Diagnostic Evaluation of Atherosclerosis in Singapore (IDEAS) study - Lee, C.-H. (2016)
American College of Cardiology Congress